2019
DOI: 10.2147/cia.s191751
|View full text |Cite
|
Sign up to set email alerts
|

<p>Handling of informed consent and patient inclusion in research with geriatric trauma patients &ndash; a matter of protection or disrespect?</p>

Abstract: Background Despite the aging of numerous societies and future health care challenges, clinical research in the elderly is underrepresented. The aim of this review was to analyze the current practice exemplary in gerontotraumatology and to discuss potential improvements. Materials and methods A literature review was performed in 2016 based on a PubMed search for gerontotraumatologic studies published between 2005 and 2015. Trials were evaluated for methodology and ethica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…This complexity leads to misunderstanding and misinterpretation of the legislation by researchers who design trials involving adults who lack capacity [ 35 ], RECs who review these trials [ 36 ] and healthcare professionals caring for these populations [ 37 ]. Current ethical guidelines fail to support the inclusion of participants unable to consent through the lack of specific and appropriate advice, which is in itself ethically problematic [ 14 ]. Further guidance is urgently needed for RECs/IRBs, the trials community, and healthcare professionals in order to improve confidence and reduce inconsistencies that act as barriers to conducting trials involving adults lacking capacity to consent.…”
Section: Challenges Of Surrogate Consentmentioning
confidence: 99%
See 3 more Smart Citations
“…This complexity leads to misunderstanding and misinterpretation of the legislation by researchers who design trials involving adults who lack capacity [ 35 ], RECs who review these trials [ 36 ] and healthcare professionals caring for these populations [ 37 ]. Current ethical guidelines fail to support the inclusion of participants unable to consent through the lack of specific and appropriate advice, which is in itself ethically problematic [ 14 ]. Further guidance is urgently needed for RECs/IRBs, the trials community, and healthcare professionals in order to improve confidence and reduce inconsistencies that act as barriers to conducting trials involving adults lacking capacity to consent.…”
Section: Challenges Of Surrogate Consentmentioning
confidence: 99%
“…Approximately 58% of the total US population are typically excluded from research studies [ 9 ], and a third of randomized controlled trials are at high risk of bias, most commonly because the clinical population used is not appropriate for the trial [ 8 ]. Exclusions of people with cognitive impairment are seen in areas such as geriatrics research [ 10 ], rehabilitation interventions after hip fracture [ 11 ], learning disabilities [ 12 ], peri-operative medicine [ 13 ], trauma [ 14 ] and neurological research [ 15 ]. Clinical trials in other areas such as emergency research also encounter significant ethical challenges around informed consent which impacts on the populations included in trials [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent review of studies on the NIHR portfolio found that 60% of the studies excluded learning disability groups, none of the studies investigating pneumonia or sepsis included learning disability groups despite being a key contributor to premature deaths, and only 1.4% of all studies were specifically related to learning disabilities [18]. Similar exclusions of people with cognitive impairment are seen in other areas of research such as geriatrics [7], rehabilitation interventions following hip fracture [19], perioperative medicine [20], trauma [21] and neurological research [22]. Under-recruitment to research into conditions such as dementia is one of the key challenges to advancing understanding of these conditions and improving the care and treatment of those who live with these conditions [23].…”
Section: Introductionmentioning
confidence: 94%